Did free market fundamentalism spawn the likes of Donald Trump? - Chakravarty, Manas (http://www.livemint.com/, 2017)
The economy was always embedded in society until capitalism arrived on the scene—this perhaps best explains the rise of Donald Trump
N/A
Keywords: BLOCK; Fred; TRUMP; Donald; double movement; market fundamentalism

Karl Polanyi on the Rise of Fascism and Market Economy - Komlik, Oleg (Economic Sociology and Political Economy, 2017)
A spectre is haunting Europe and the world — the spectre of Fascism (veiled as defensive democracy and common-sense patriotism) and authoritarian neoliberalism (disguised as social protectionism an…
Sociology
Keywords: economic sociology; fascism

A Foreword to Kari Polanyi Levitt - Rodrick, Dani (Dani Rodrik's weblog, 2017)
I was recently asked to write a foreword to the Mexican edition of Kari Polanyi Levitt’s From the Great Transformation to the Great Financialization. Kari is Karl Polanyi's daughter, and the essays in her book – part memoir, part intellectual...
N/A
Keywords: From the Great Transformation to the Great Financialization (Book); POLANYI LEVITT; Kari; embeddedness; neoliberalism